Evaluation of Leachate Quality at Municipal Solid Waste Landfill Site: Case Study in Sliwung, Situbondo Regency, East Java, Indonesia - Khoiron; Ari Probandari; Wiwik Setyaningsih; Heru Subaris Kasjono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: This study aims to evaluate the quality of landfill leachate that has been treated in a wastewatertreatment plant.Mathods: Leachate samples were taken for 12 months (January-December) in 2018. The leachate qualityparameters studied were: BOD5, COD, TSS, total N, and heavy metals (Hg and Cd).Results: The results showed that the BOD5 quality met environmental quality standards in May, June, July,September, October and December, COD exceeded environmental quality standards, TSS met environmentalquality standards in February, March, August, and December, N total met quality standards environment for11 months, only December did not meet environmental quality standards, heavy metals (Cd and Hg) werebelow environmental quality standards.Conclusion: The Sliwunglandfill to conduct an approach study that can reduce the BOD5, COD, and TSSvalues so that they do not exceed the specified quality standards.